Nucleotide Sequence Context Effect of a Cyclobutane Pyrimidine Dimer upon RNA Polymerase II Transcription - Tornaletti, Silvia (1997)
We have studied the role of sequence context upon RNA polymerase II arrest by a cyclobutane pyrimidine dimer using an in vitro transcription system consisting of templates containing a specifically located cyclobutane pyrimidine dimer (CPD) and purified RNA polymerase II (RNAP II) and initiation factors. We selected a model sequence containing a well characterized site for RNAP II arrest in vitro, the human histone H3.3 gene arrest site. The 13-base pair core of the arrest sequence contains two runs of T in the nontranscribed strand that impose a bend in the DNA. We hypothesized that arrest of RNAP II might be affected by the presence of a CPD, based upon the observation that a CPD located at the center of a dA(6)·dT(6) tract eliminates bending (Wang, C.-I., and Taylor, J.-S. (1991) Proc. Natl. Acad. Sci. U. S. A. 88, 9072–9076). We examined the normal H3.3 sequence and a mutant sequence containing a T → G transversion, which reduces bending and efficiency of arrest. We show that a CPD in the transcribed strand at either of two locations in the arrest site is a potent block to transcription. However, a CPD in the nontranscribed strand only transiently pauses RNAP II. The CPD in concert with a mutation in the arrest site can reduce the extent of bending of the DNA and improve read through efficiency. These results demonstrate the potential importance of sequence context for the effect of CPDs within transcribed sequences.